Keterlibatan Generasi Muda Dalam Demokrasi Dan Pemilu 2024 - Diana Azzahra; Rakha Fairuz Sakhi; Ulya Fathiah Kamila; Putri Chahyani; Akbar Habibi (Universitas 45 Surabaya, 2024)
This research aims to explain the involvement of the younger generation in democracy and the 2024 elections. Political participation determines the quality of politics that will be led by future state leaders. This research shows that the young generation is currently dominating the 2024 elections. Elections are a means of implementing people's sovereignty which are held directly. As agents of change, the younger generation can have a big impact on change for the Indonesian nation. This research uses a descriptive method with a qualitative approach, with data collection through literature studies that encourage the involvement of the younger generation in democracy and elections.